A Comparative Study on the Effect of Artemisia and Clotrimazole Vaginal Cream on Vaginal Candida Infection on Non-Pregnant Women in Fertile Age in Mashhad in 2016-2017: A Triple Blind Clinical Trial - S Ebrahimzadeh Zgemi; N Golmakani; MJ Asili; A Naseri; Z Mohebbi Dehnavi; Z Kamali; A Saber Mohammad (Institue of Medicinal Plants, ACECR, 2019)
Background: About 75% of women experience at least one vulvovaginal candidiasis during their life. Clotrimazole is an antifungal drug that has side effects along with its therapeutic properties. For this reason, a large percentage of women tend to use natural herbal treatments. Artemisia is an anti-fungal activity. Objective: The aim of this study was to compare the effect of Artemisia vulgaris and Clotrimazole on vaginal candida infection on non pregnant women in fertility ages. Methods: This study is a triple blind clinical trial performed on 72 non-pregnant women in Mashhad in 2016-2017 years. The research units were divided into two groups (receiving Artemisia Vaginal Cream and receiving Clotrimazole Vaginal Cream). After confirmation of candidacy and having consent for participation, by random allocation and treated for seven nights. After the treatment, the data was analyzed using SPSS software (version 24). Results: After treatment, the score for candidate vaginal symptoms was not significant in Artemisia and Clotrimazole group based on Mann-Whitney test (P = 0.518). The Wilcoxon test showed a significant reduction in the symptoms of vaginal candida infection before and after treatment in both groups of Artemisia (P <0.001) and clotrimazole (P <0.001). Conclusion: Due to the similar effects of Artemisia and Cholitrimazole, Artemisia can be used as an alternative treatment for vaginal candidiasis due to less side effects.